Industries textiles : un patrimoine fragile - Nadine Halitim-Dubois (In Situ)
The Lyon silk industry has left a broad selection of heritage. This article will take a look at a selection of four examples in order to illustrate the inherent difficulties in heritage conservation. The Mattelon workshop, the last family-run silk weaving business in Lyon, characteristic of the innumerable domestic workshops in the city during the nineteenth century, was given statutory protection as a historic monument in 1996. The silk-weaving looms from the former municipal weaving school did not have such a happy fate. Sixteen of them were indeed protected as historic monuments in 1996 but only four of these, protected at the higher level as ‘classified’ monuments, survive today; the remaining twelve were only given the lower level of protection as ‘inscribed’ monuments, and they were subsequently destroyed, by mistake. The Lyon textile museum, the Musée des Tissus, holds a rare collection of enamelled plates coming from the ‘Talabot-Persoz-Rogeat’ driers, designed by the industrialist, Rogeat, in 1853. His driers limited fraud by avoiding the addition of water to silk in order to increase its weight artificially. Finally, a ‘magnanerie’, an installation for silk-worm breeding, was created during the 1970s at La Mulatière, a suburb near Lyon. This became the Unité nationale séricicole, the national sericicultural establishment, with an authentic conservatory of mulberry trees and different varieties of silkworms. But in 2009, this department was closed down by the University of Lyon 1 (Institut national de Recherche agronomique, INRA). Its silk-related holdings were transferred to similar organisations in Italy and in Japan, whilst solutions are still being looked for in the Lyon region for the preservation of a part, at least, of its mulberry collection.